The Effect of Combined Music Therapy and Stress Ball on Pain During Vascular Access Cannulation in Hemodialysis Patients - Hindri Royiah Fatma; Rohman Azzam; Ninik Yunitri; Yani Sofiani; Yuni shahroh (Indonesian Journal of Global Health Research, 2025)
Hemodialysis remains the main therapy for patients with kidney failure. During the cannulation process, which is the insertion of a needle into a vascular access, hemodialysis patients often experience pain. The combination of music therapy and the use of stress balls is an example of a non-pharmacological intervention that can be used to overcome pain during cannulation. Objective to identify the effectiveness of the combination of music therapy and stress balls on pain in hemodialysis patients during the vascular access cannulation process. This study used a phased cross-over design, where each respondent received both treatments alternately. A total of 42 respondents were divided into two groups: the experimental group (n = 21) received music therapy and stress balls , while the control group (n = 21) received standard hospital therapy, namely deep breathing relaxation. Furthermore, the two groups exchanged treatments. The level of pain was measured using a VAS (Visual Analog Scale). The results showed that the combination of music therapy and stress balls was effective in reducing pain during the cannulation process, with significant changes in pain levels after insertion (p < 0.001). Cohen's d effect size of -0.632 indicates that combination therapy has a stronger effect in reducing pain than deep breathing relaxation therapy.